2006
DOI: 10.1038/sj.emboj.7600963
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+-activated cation channel TRPM4 is regulated by phosphatidylinositol 4,5-biphosphate

Abstract: Transient receptor potential (TRP) channel, melastatin subfamily (TRPM)4 is a Ca 2 þ -activated monovalent cation channel that depolarizes the plasma membrane and thereby modulates Ca 2 þ influx through Ca 2 þ -permeable pathways. A typical feature of TRPM4 is its rapid desensitization to intracellular Ca 2 þ ([Ca 2 þ ] i ). Here we show that phosphatidylinositol 4,5-biphosphate (PIP 2 ) counteracts desensitization to [Ca 2 þ ] i in inside-out patches and rundown of TRPM4 currents in whole-cell patch-clamp exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
356
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(371 citation statements)
references
References 38 publications
12
356
3
Order By: Relevance
“…The previously proposed modulation sites for phosphorylation, PtdInsP 2 binding or calmodulin binding at the C-terminal domain do not appear to be accessible based on the structure 14,16 . However, the structural feature of the C-terminal domain would imply that the coiled coil is capable of undergoing an up-and-down sliding motion, which, in turn, can induce lateral movement through the stretcher helices and propagate to the channel transmembrane pore through the middle tier LHD (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The previously proposed modulation sites for phosphorylation, PtdInsP 2 binding or calmodulin binding at the C-terminal domain do not appear to be accessible based on the structure 14,16 . However, the structural feature of the C-terminal domain would imply that the coiled coil is capable of undergoing an up-and-down sliding motion, which, in turn, can induce lateral movement through the stretcher helices and propagate to the channel transmembrane pore through the middle tier LHD (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Upon Ca 2+ activation, TRPM4 is desensitized to a steady state within a minute at both negative and positive membrane potentials. This TRPM4 desensitization was attributed to the loss of phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P 2 ) in the membrane due to Ca 2+ -activated phospholipase C 13,14 . At the Ca 2+ -desensitized steady state, TRPM4 exhibits voltage-dependent gating with higher channel open probability at depolarizing membrane potential 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, in contrast to the electrophysiological properties of the overexpressed channel, which include channel activation at positive potentials and channel closure at negative potentials 17 . However, the voltage dependence of TRPM4 relies critically on phosphatidylinositol-4,5-bisphosphate in the plasma membrane 37,38 ; endogenous phosphatidylinositol-4,5-bisphosphate quantities might work more effectively with endogenous amounts of TRPM4 protein in primary mast cells rather than the overexpressed TRPM4 in HEK293 cells. It is notable that mice lacking type I phosphatidylinositol phosphate kinase, the enzyme that synthesizes phosphatidylinositol-4,5-bisphosphate, have greater mast cell degranulation similar to that of Trpm4 -/-mice 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Clapham and colleagues (2002) suggested that receptormediated PIP 2 is required to maintain TRPM7 activity, and its breakdown by receptormediated stimulation of phospholipase C (PLC) is responsible for the inhibition TRPM7 they observed when stimulating cells with agonists that couple to PLC. Although several ion channels, including members of the TRPM family [TRPM4 (Zhang et al 2005;Nilius et al 2006), TRPM5 (Liu and Liman 2003), and TRPM8 (Liu and Qin 2005;Rohacs et al 2005)] are subject to PIP 2 -mediated regulation, the case for TRPM7 has not been made without ambiguity. Most of the experiments presented in support of PIP 2 regulation were performed in cells that overexpress TRPM7 or with receptor agonists that can couple to PLC (or both).…”
Section: Regulation By Receptor Stimulationmentioning
confidence: 99%